Investigation on Transient Characteristics of High Pressure Vessel Water Level Measurement - Wang, Meng; Chen, Wenzhen; Fan, Guangming (Frontiers in Energy Research, 2021)
An experimental study was conducted on the characteristics of high pressure vessel water level systems at both fast and slow depressurization states. The swollen and collapsed water levels were observed experimentally. The test results show that the swollen water level has a relatively fixed difference compared to the collapsed one for the transient of both high and low depressurization rates. Under the conditions of steady and heat up, the differences between the swollen and collapsed water levels are acceptable. For the transients of depressurization, the outputs from the three channels of the inside vessel double-reference-tube water level system have a great deal of differences between each other because of the thermal inertia of the two reference tubes and the water levels in the cistern. In view of nuclear power plant safety and operation, the outside vessel single-reference-tube water level system used in the current pressurizer is adequate and the inside vessel double-reference-tube water level system is suggested as an additional reference to monitor the water level in the steam generator.